The influence of the project for strengthening the profile of Pancasila Students on increasing Students' environmental care attitudes at SMP Islam Gandusari, Trenggalek - Fatmawati, Nofi; Khusna, Nur Isroatul (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
The current environmental conditions are very worrying and cause various problems. Environmental problems are caused by human greed and lack of concern and responsibility in utilizing nature. Efforts to overcome this problem are by implementing environmental education through the Strengthening Pancasila Students Profile (P5) Project activities with the theme of sustainable living. Because all levels of society must share a caring attitude towards the environment, including students, this research aims to determine how implementing the P5 theme of sustainable living increases students' environmental care attitudes. This research approach uses a quantitative associative type in the form of a cause-and-effect relationship. The research location at Gandusari Trenggalek Islamic Junior High School is in Melis Village, Gandusari District, Trenggalek Regency. The sampling technique used proportional random sampling with 44 respondents from all 123 class VIII students. Data collection uses interviews, questionnaires, and documentation. The research results show that implementing the P5 theme of sustainable living entitled " Hijau Tamanku Asri Sekolahku (my green garden, my beautiful school)" influences increasing students' environmental care attitudes by 35.4 percent. This research has implications for educational units that implement the P5 theme of sustainable living because it can increase students' environmental care attitudes to overcome environmental problems.